2015
DOI: 10.1080/2162402x.2015.1019981
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating T lymphocytes improve clinical outcome of therapy-resistant neuroblastoma

Abstract: Neuroblastoma grows within an intricate network of different cell types including epithelial, stromal and immune cells. The presence of tumor-infiltrating T cells is considered an important prognostic indicator in many cancers, but the role of these cells in neuroblastoma remains to be elucidated. Herein, we examined the relationship between the type, density and organization of infiltrating T cells and clinical outcome within a large collection of neuroblastoma samples by quantitative analysis of immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
127
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(142 citation statements)
references
References 54 publications
9
127
0
1
Order By: Relevance
“…37 Further, for most tumor types there is a large body of data indicating that the concentration of T cells in tumors (TIL) correlates with favorable outcome. [38][39][40] In addition to antitumor efficacy in vivo, increased tumor cell killing activity of combination treatment-derived splenocytes ex vivo suggest the presence of active antitumor T cells on a systemic level. Previously, we have shown that adenovirus improved the efficacy of adoptive T-cell transfer in mice by increasing the number of IFNg-expressing CD8…”
Section: Discussionmentioning
confidence: 99%
“…37 Further, for most tumor types there is a large body of data indicating that the concentration of T cells in tumors (TIL) correlates with favorable outcome. [38][39][40] In addition to antitumor efficacy in vivo, increased tumor cell killing activity of combination treatment-derived splenocytes ex vivo suggest the presence of active antitumor T cells on a systemic level. Previously, we have shown that adenovirus improved the efficacy of adoptive T-cell transfer in mice by increasing the number of IFNg-expressing CD8…”
Section: Discussionmentioning
confidence: 99%
“…For example, Galon et al described the combination of CD8 + cellular infiltrates and CD45RO + cellular infiltrates to formulate a prognostically significant "immunoscore" in colon cancer. 27 In fact, naturally occurring tumorinfiltrating lymphocytes have been associated with better patient survival in numerous cancer types [28][29][30] and may also correlate with better responsiveness to checkpoint inhibition. 31 In addition, predictive biomarkers of response are likely to depend on the type of immunotherapy used.…”
Section: Discussionmentioning
confidence: 99%
“…Another, as yet relatively underexplored, area for prognostic factors relates to the host and tumor microenvironment rather than factors intrinsic to tumor cells themselves. For example, the extent of tumor infiltration by T cells or macrophages is correlated with outcome. Expression of different isoforms of the NK‐cell receptor NKp30 also correlates with EFS in patients with HR‐NBL who have responded to induction chemotherapy .…”
Section: Potential Prognostic Factors For Use In Substratification Ofmentioning
confidence: 99%
“…Of these three possible endpoints (A, B, or C), the continuous time‐to‐event endpoint would appear to be the most informative. In an analysis of INRG data, an approach using a binary endpoint [B] failed and was replaced by a successful analysis with a continuous time‐to‐event endpoint [A]. In an analysis exploring the potential utility of copy‐number profile for risk substratification, a binary endpoint [C] was used to identify a signature of UHR‐NB, but this signature was not validated in a separate patient cohort …”
Section: The Challenge Of Selecting the Most Appropriate Endpointmentioning
confidence: 99%